Characteristics and drivers of carbon emissions intensity vary across countries and time: evidence from 210 countries worldwide - Xu Pengfei; Chen Xiaotong; Chen Jingling (Ecological Indicators)
Carbon emission intensity (CEI) functions as a pivotal metric for evaluating carbon efficiency, thereby playing a critical role in the promotion of sustainable development and the mitigation of climate change. The present study investigates CEI dynamics in 210 countries from 2000 to 2023 using the Mann-Kendall test, Theil-Sen median analysis, and Hurst index, complemented by machine learning to decode driving mechanisms. The findings indicate a substantial global escalation in carbon emissions, amounting to over 39.6 % during the past two decades, concomitant with a 7 % augmentation in CEI. The analysis also underscores considerable variations in CEI trends among countries. A salient finding is that over 92 % of developed nations have witnessed a decline in CEI, while more than 52 % of less developed countries persist in experiencing increases. Moreover, factors such as population density, urban–rural population dynamics, and urban land expansion are of greater significance at the global level. Furthermore, developed countries demonstrate heightened sensitivity to factors such as final consumption expenditure and urban–rural population dynamics. In contrast, the CEI of emerging economies is more influenced by indicators related to technological innovation.